2008
DOI: 10.1111/j.1600-0560.2008.00990.x
|View full text |Cite|
|
Sign up to set email alerts
|

Localized lymphedema (elephantiasis): a case series and review of the literature

Abstract: Background:  Lymphedema typically affects a whole limb. Rarely, lymphedema can present as a circumscribed plaque or an isolated skin tumor. Objective:  To describe the clinical and pathologic characteristics and etiologic factors of localized lymphedema. Methods:  Case–control study of skin biopsy and excision specimens histologically diagnosed with lymphedema and presenting as a localized skin tumor identified during a 4‐year period. Results:  We identified 24 cases of localized lymphedema presenting as solit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 125 publications
2
48
1
Order By: Relevance
“…Lu et al 37 identified histopathologic features of localized lymphedema in a variety of conditions, with variable factors including trauma, surgery, chronic inflammatory disease, and bacterial cellulitis. Paul and The same group has recently posited that localized lymphedema is an essential pathogenic factor in verruciform xanthomas.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al 37 identified histopathologic features of localized lymphedema in a variety of conditions, with variable factors including trauma, surgery, chronic inflammatory disease, and bacterial cellulitis. Paul and The same group has recently posited that localized lymphedema is an essential pathogenic factor in verruciform xanthomas.…”
Section: Discussionmentioning
confidence: 99%
“…In its earliest stages, lymphedema is soft and pitting; however, with persistence, lymphedema has a brawny, non-pitting appearance likened to peau d'orange because of accentuation of skin folds and follicular ostia. Most of the swelling occurs in the subcutaneous tissue, but the skin exhibits the most changes, which, when severe, is termed elephantiasis [1]. Elephantiasis described a gross enlargement of the part of the body that has been involved.…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al [1] presented a clinical series of 24 cases of localised lymphedema; he made a comparison between those patients and the patients with diffuse lymphedema. Lu found that the most frequent localisation in these patients is anogenital, and overall, women were more frequently affected by lymphedema, particularly in the anogenital region and trunk, than men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, a chronic localised lymphoedema presenting as a neoplastic mass is a rare condition. Lu et al [2] reported a series of 24 cases of localised lymphoedema (elephantiasis) presenting as solitary large polyps, plaques and pendulous swellings, some mimicking a soft tissue tumour. In this series, anogenital involvement was most frequent, particularly in the vulvar region.…”
Section: Discussionmentioning
confidence: 99%